EDELWEISS - Kraus, H; Collaboration, EDELWEISS (2012)
The EDELWEISS-II collaboration has performed a direct search for WIMP dark matter with an array of ten 400 g heat-and-ionization cryogenic detectors equipped with interleaved electrodes for the rejection of near-surface events. Results from eleven months of continuous operation at the Laboratoire Souterrain de Modane are shown and their interpretation in terms of limits on the cross-section of spin-independent interactions of WIMPs and nucleons presented. The result obtained demonstrates the excellent background rejection capabilities of these simple and robust detectors in an actual WIMP search experiment. © 2012 American Institute of Physics.